ASSESSMENT AND RESERVES FOR INCREASING LOYALTY OF ENTERPRISE STAFF - CHEREP, OLEKSNDR; TOMAREVA-PATLAKHOVA, VIKTORIIA; KABANOVA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article deals with the level of loyalty of the personnel of construction enterprises. The comprehensive methodology. recommendations for its improvement are developed. The comprehensive methods include the following methods: assessing staff turnover, determining the degree of team cohesion, assessing the state of moral and psychological climate, determining the level of work discipline, assessing the level of motivation based on self-esteem and direct assessment of loyalty by L. Porter’s method "Organizational Loyalty Questionnaire" V. Dominyak. The base of the study was five enterprises of Zaporizhia, the main type of economic activity of which according to the NACE belongs to group 42.2 "Construction of communications". Among the surveyed organizations were medium and small enterprises, the total number of employees of which was 487 people. The application of a comprehensive methodology for assessing the level of loyalty of construction personnel allowed to determine that the average corresponds to a satisfactory level, due to: the average level of group cohesion of labor collectives; unsatisfactory state of moral and psychological climate in small production groups; the absence of any programs at enterprises to ensure and improve labor discipline of staff; low level of motivational influence of organizational culture and the desire for self-realization of workers. Solving certain problems of the internal environment of enterprises will significantly increase the level of staff loyalty. The main directions of organizational change should be: conducting team-building activities; control and improvement of working conditions of staff; moral and material incentives for staff; analysis and forecasting of potential loyalty / disloyalty of new employees; development of a program for adaptation of new employees; development of methods of working with disloyal staff; development of a program for the development and improvement of professional competencies of staff; improvement and development of organizational culture of enterprises; formation of loyalty of the personnel of the enterprises through realization of the program of social responsibility.